Exercise training decreases oxidative stress in skeletal muscle of rats with pulmonary arterial hypertension. (3rd September 2022) - Becker, C. U.; Sartório, C. L.; Campos-Carraro, C.; Siqueira, R.; Colombo, R.; Zimmer, A.; Belló-Klein, A.
Abstract: The effects of exercise training on oxidative stress in gastrocnemius of rats with pulmonary hypertension were studied. Four groups were established: sedentary control (SC), sedentary monocrotaline (SM), trained control (TC), trained monocrotaline (TM). Exercise was applied for 4 weeks, 5 days/week, 50–60 min/session, at 60% of VO2 max. Right ventricular (RV) pressures were measured, heart and gastrocnemius were removed for morphometric/biochemical analysis. Lipid peroxidation (LPO), H2 O2, GSH/GSSG, and activity/expression of antioxidant enzymes were evaluated. Increased RV hypertrophy, systolic and end-diastolic pressures (RVEDP) were observed in SM animals, and the RVEDP was decreased in TM vs. SM. H2 O2, SOD-1, and LPO were higher in the SM group than in SC. In TM, H2 O2 was further increased when compared to SM, with a rise in antioxidant defences and a decrease in LPO. GSH/GSSG was higher only in the TC group. Exercise induced an efficient antioxidant adaptation, preventing oxidative damage to lipids.